2013
DOI: 10.1371/journal.pone.0068701
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Receptors in Human Airway Smooth Muscle Cells: Activation by TLR1/2, TLR3, TLR4, TLR7 and NOD1 Agonists

Abstract: BackgroundPattern-recognition receptors (PRRs), including Toll-like receptors (TLRs), NOD-like receptors (NLRs) and RIG-I-like receptors (RLRs), recognize microbial components and trigger a host defense response. Respiratory tract infections are common causes of asthma exacerbations, suggesting a role for PRRs in this process. The present study aimed to examine the expression and function of PRRs on human airway smooth muscle cells (HASMCs).MethodsExpression of TLR, NLR and RLR mRNA and proteins was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 53 publications
1
38
1
Order By: Relevance
“…Using the same concentration of IRS661 as previously used in vitro (5), we were unable to see any effect on imiquimod-induced bronchodilation. Although we did not confirm the ability for IRS661 to inhibit TLR7 in this study, we have previously confirmed its ability to inhibit TLR7-mediated responses in isolated airway smooth muscle cells (11). In addition, we showed that the TLR7 agonist CL264 failed to induce relaxation or inhibit histamine-induced Ca 2ϩ flux, which would dispute a role for TLR7.…”
contrasting
confidence: 70%
“…Using the same concentration of IRS661 as previously used in vitro (5), we were unable to see any effect on imiquimod-induced bronchodilation. Although we did not confirm the ability for IRS661 to inhibit TLR7 in this study, we have previously confirmed its ability to inhibit TLR7-mediated responses in isolated airway smooth muscle cells (11). In addition, we showed that the TLR7 agonist CL264 failed to induce relaxation or inhibit histamine-induced Ca 2ϩ flux, which would dispute a role for TLR7.…”
contrasting
confidence: 70%
“…This is corroborated by the finding that, in our models, imiquimod-mediated bronchodilation of guinea pig airways was not dependent on TLR7, as both in vitro and in vivo administration of the TLR7 antagonist IRS661 had no effect on imiquimod-mediated bronchodilation. This was true even when the antagonist was used at in vitro concentrations 100-fold higher than previously shown to be effective (27). Additionally, another TLR7 agonist, CL264, that we and others (7,19) have shown to be more potent than imiquimod in terms of TLR7 agonism had no effect on precontracted airways or on histamine-induced Ca 2ϩ mobilization in ASM cells.…”
Section: Discussionmentioning
confidence: 57%
“…Imiquimod has previously been shown to upregulate cytokine and chemokine production and alter cell-surface marker expression on ASM, effects that were evident after 24 h (27). However, the speed at which imiquimod exerts its effect would suggest that the effect on ASM does not occur via traditional TLR-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study, to my knowledge, to report that NOD1 activation upregulates the adhesion molecules in adipose tissue. However, ligand activation of NOD1 has been shown to increase ICAM1 gene expression in human airway smooth muscle cells (Kvarnhammar et al 2013), bronchial epithelial cells (Wong et al 2013) and human coronary artery endothelial cells (Nishio et al 2011). In vivo, NOD1 ligands induce ICAM1 and VCAM1 gene expression in the aortic root, pulmonary artery, aorta and spleen (Nishio et al 2011).…”
Section: Figurementioning
confidence: 99%